Radios quichuas en el proceso migratorio y el fortalecimiento cultural del pueblo Cañari en migración - Muñoz Chimborazo, Raúl Clemente (2020)
This research focuses on analyzing the role played by the Quichua radio stations, Radio La Voz de Ingapirca of Cañar and Radio El Tambo Stereo in the United States, in accompanying the migration process and strengthening the culture of the indigenous population of the Quichua Cañari ethnic group that migrated to the United States during the last four decades. In order to achieve these objectives, qualitative research methodology was applied, from the perspective of phenomenology and ethnography, to analyse the content of in-depth interviews with managers, announcers and listeners of the two stations. The study concludes that the stations are very close to the Cañari people; they implemented strategies and actions to accompany and link the migrant and his family during the migration process; in addition, they motivated and accompanied the recovery and revitalization of cultural elements such as language, identity, music and traditional festivals of the Cañari people located in the northeastern United States.